2014
DOI: 10.1007/s00595-014-0980-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological factors predicting R0 resection and long-term survival after esophagectomy in patients with T4 esophageal cancer undergoing induction chemotherapy or chemoradiotherapy

Abstract: Patients showing an early tumor response to induction treatment and improvement of dysphagia may be appropriate candidates for esophagectomy, and individualized postoperative management strategies should be developed for patients with initially unresectable T4 esophageal cancer who have ≥ 2 positive nodes post-treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Based on these results, SOCS1 gene therapy may represent a new treatment for ESCC by inducing a variety of antitumor mechanism. For locally advanced ESCC that has invaded adjacent indispensable organs, although chemoradiotherapy is reported to be the first treatment choice, local disease control may be difficult to achieve in some cases . Our findings demonstrate that SOCS1 gene therapy might be facilitated by administering in multiple sites of the tumor using endoscopy.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Based on these results, SOCS1 gene therapy may represent a new treatment for ESCC by inducing a variety of antitumor mechanism. For locally advanced ESCC that has invaded adjacent indispensable organs, although chemoradiotherapy is reported to be the first treatment choice, local disease control may be difficult to achieve in some cases . Our findings demonstrate that SOCS1 gene therapy might be facilitated by administering in multiple sites of the tumor using endoscopy.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, although multidisciplinary treatment with a focus on radiation therapy is also performed as an important treatment option for patients with T4 tumor, almost 50% of patients develop a locoregional recurrence after chemoradiotherapy . Additionally, salvage surgery after radiation therapy may cause serious problems, such as increased risk of surgery‐related adverse events and mortality . Therefore, new regional approaches that can improve the prognosis of patients with locally advanced ESCC are needed.…”
mentioning
confidence: 99%
“…Five of 28 patients underwent esophagectomy via right thoracotomy and 23 underwent TE. Primary tumor presenting as a bulky mass convexly compressing neighboring organs with an indistinct soft density layer bordering the tumor on computed tomography (CT) was regarded as initially unresectable T4 tumor . In addition, tumors were diagnosed as clinical T4 if they extended into the lumen or caused a deformity of the tracheobronchus or if they were attached to the aorta at a contact angle of ≥90° in over three slices .…”
Section: Methodsmentioning
confidence: 99%
“…The poor results of dCRT in unresectable cT4 tumors and the morbidity of salvage surgery following dCRT have led to the hypothesis that planned surgery after induction CRT may be a reasonable alternative. In this regard, recent studies have shown that it is feasible to perform a radical resection, while preserving vital organs (trachea and aorta), in patients with tumor response to induction treatment . However, radical esophagectomy after induction therapy in these patients has been associated with a higher risk of in‐hospital mortality .…”
Section: Stage‐directed Individualized Therapymentioning
confidence: 99%
“…However, radical esophagectomy after induction therapy in these patients has been associated with a higher risk of in‐hospital mortality . Nonetheless, reported R0 resection rates range between 61% and 88% . As this is a rather new strategy, identifying prognostic indicators for R0 resections could contribute to a better selection of appropriate candidates for esophagectomy after induction therapy in patients with initially unresectable cT4 tumors, although secondary radical esophagectomy after induction therapy has been associated with a higher risk of in‐hospital mortality …”
Section: Stage‐directed Individualized Therapymentioning
confidence: 99%